Consumption, Capital, and Class in Digital Space: The Political Economy of Pay-per-Click Business Models. Issue 2 (3rd April 2021) - Azhar, Shahram
Abstract : Theories of digital capitalism explore two interrelated conceptual problems: how seemingly "free" use of social-networking websites is compatible with capitalist commodity production and how the Marxian class-exploitation conceptual apparatus can be extended to understand newly emerging digital social relations. This essay's dialectical approach problematizes digital production in relation to digital consumption, connecting these two moments to the organization of the surplus in digital space via a fundamental and subsumed class framework. A link is shown between capitalist and noncapitalist human activity in digital space, distinguishing between commodity and noncommodity forms and displaying the dialectic of free versus forced consumption. This identification is nonneutral to how we conceptualize digital production and class relations. While clients consume commodities, users are lured into providing the conditions of existence (network formation; e.g., Facebook) necessary for this concrete form of capital to accumulate, globally extracting unpaid surpluses from direct producers via capitalist as well as noncapitalist modes of appropriation and distribution.